P3.191 Hiv in indigenous msm in guatemala: a hidden problem. (8th July 2017) - Mendizabal-Burastero, Ricardo; Mendizabal-Burastero, Ricardo; Yancor, Marco Polo
Abstract : Introduction: In Guatemala, data regarding HIV epidemics doesn't show much data about indigenous population, although nearly 50% of the population in Guatemala are indigenous. In metropolitan area, MSM HIV prevalence is around 9%. But there is not data about HIV prevalence in indigenous MSM. This data is the first report in this important group. Methods: Cross-sectional data analysis from October 2015 to July 2016. MSM were recruited as part of the implementation of Global Fund projects. Activities were implemented in three department of the Guatemalan highlands: Sololá, Totonicapan and Chimaltenango. Recruitment was performed by peers, by face-to-face or using social networks. Rapid HIV testing was performed in-site and confirmation in reference laboratory, STI were evaluated by syndromic management. Data was analysed using Stata 13. Results: 1196 MSM were tested for HIV and 293 had STI evaluation. 42% lived in Chimaltenango and 19% in Solola. Median age was 22 years old (IQR 19–26); 40.3% of them self-reported as indigenous, 11% of them K'iche' and 10% kakchiquel. 60% of them had high school or higher education, 58 HIV cases were diagnosed, for a global HIV prevalence of 4.8%. In indigenous MSM HIV prevalence was higher (5.1 vrs 4.9, no difference). In K'iche' MSM (N:156) HIV prevalence was higher (4.2%) than in kakchiquel (3.9%), but no difference. 18% had an STI, the most prevalent were anal warts (13%). Conclusion: HIV prevalence in indigenous MSM is lower than reported in Guatemala city, however is a major public health problem not previously reported in Guatemala. Population representative studies in the highlands are needed to asses HIV prevalence in MSM, as well to improve current interventions.